Author Correction: Enhancer decommissioning by LSD1 during embryonic stem cell differentiation. (25th October 2018) - Whyte, Warren; Bilodeau, Steve; Orlando, David; Hoke, Heather; Frampton, Garrett; Foster, Charles; Cowley, Shaun; Young, Richard
In this Letter, the western blot for LSD1 in the right panel of Fig. 2b ('TCP +') was inadvertently duplicated from the tubulin blot immediately below. The actual tubulin western blot shows the same result, with no significant change to the levels of tubulin (see Fig. 1 of this Amendment). In addition, the western blots for LSD1 and HDAC1 of Fig. 3b and c have been corrected to include vertical black lines to delineate the juxtaposition of lanes that were non-adjacent in the original blotting experiment (see Fig. 2 of this Amendment). Supplementary Figs. 4a, 6b and 9b have also been corrected to delineate non-adjacent lanes with vertical black lines (see Supplementary Information of this Amendment). The complete raw data images from these western blotting experiments can also be found in the Supplementary Information of this Amendment. The original Letter has not been corrected.